Acoustic Change Responses to Amplitude Modulation in Cochlear Implant Users: Relationships to Speech Perception - Han, Ji-Hye; Dimitrijevic, Andrew (Frontiers in Neuroscience, 2020)
Objectives: The ability to understand speech is highly variable in people with cochlear implants (CIs) and to date, there are no objective measures that identify the root of this discrepancy. However, the behavioral measures of temporal processing such as the temporal modulation transfer function (TMTF) has previously found to be related with vowel and consonant identification in CI users. The acoustic change complex (ACC) is a cortical auditory-evoked potential response that can be elicited by a “change” in an ongoing stimulus. In this study, the ACC elicited by amplitude modulation (AM) change was related to measures of speech perception as well as the amplitude detection threshold in CI users. Methods: Ten CI users (mean age: 50 years old) participated in this study. All subjects underwent behavioral speech tests in both quiet and noise conditions, and amplitude detection thresholds were measured to obtain the TMTF for each subject. CI users were categorized as ‘good’ (n = 6) or ‘poor’ (n = 4) based on their speech-in noise score (<50%). 64-channel electroencephalography recordings were conducted while AM sounds were presented in a free field setting. The stimulus was white noise with four different AM rates (4, 40, 100, and 300 Hz). Results: Behavioral results show that AM detection thresholds in CI users were higher compared to the normal-hearing (NH) group for all AM rates. The electrophysiological data suggest that N1 responses were significantly decreased in amplitude and their latencies were increased in CI users compared to NH controls. In addition, the N1 latencies for the poor CI performers were more prolonged than those for the good CI performers. The N1 latency for 40 Hz AM was correlated with various speech perception measures. Conclusions: Our data suggest that the ACC to AM change provides an objective index of speech perception abilities that can be used to explain the variation in speech understanding among CI users.